1979
DOI: 10.1038/bjc.1979.165
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in melanoma incidence

Abstract: Summary.-The incidences of malignant melanoma recorded by 59 populationbased cancer registries were investigated to determine the effects of racial and skincolour differences. White populations exhibited a wide range of melanoma incidences and females commonly, though not invariably, had a higher incidence than males. Non-white populations experienced in general a much lower incidence of melanoma although there was some overlap of white and non-white rates. No predominant sex difference emerged among non-white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
2
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 17 publications
3
46
2
1
Order By: Relevance
“…Regression analyses showed that this trend with latitude was significant in both males and females (Table I). An earlier analysis of these data of the melanoma incidence among Caucasians indicated that the melanoma incidence was directly related to that of cancer of all sites (excluding non-melanoma skin tumours) (Crombie, 1979). It Within Europe the relationship between melanoma incidence and latitude takes a different form (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Regression analyses showed that this trend with latitude was significant in both males and females (Table I). An earlier analysis of these data of the melanoma incidence among Caucasians indicated that the melanoma incidence was directly related to that of cancer of all sites (excluding non-melanoma skin tumours) (Crombie, 1979). It Within Europe the relationship between melanoma incidence and latitude takes a different form (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The incidence among darkskinned races is commonly low (Oettle, 1]966;Camain et al, 1972) and a clear relationship between the density of skin pigmentation and the incidence of melanoma on the exposed body sites has been demonstrated (Crombie, 1979). Melanin pigmentation is thought to afford protection by absorbing the UV (Quevedo et al, 1975) so that the degree of protection would be expected to depend on the concentration of pigment.…”
mentioning
confidence: 99%
“…18,19 Nevertheless, the protection of increased pigmentation has been hypothesized to explain the less risk to ocular melanoma in darkly pigmented people when compared with whites people. 20 In the United States, uveal melanoma primarily affects patients between 60 and 70 years old. 6 However, it has been observed that Chinese patients with uveal melanoma tended to be younger than their Western counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier paper in this series found that among the 48 "white" registries, females had a significantly higher incidence of melanoma than males (Crombie, 1979b). Details of the distribution of melanoma among the 4 major body sites (head, upper limb, lower limb and remainder) are available only for 37 "white" registries, but these also show that females have the significantly higher incidence (Table I).…”
Section: Reliability Of the Datamentioning
confidence: 97%
“…It is well known that dark-skinned races have a low incidence of melanoma (Oettle, 1966;Camain et al, 1972) and a recent study (Crombie, 1979b) has demonstrated a clear relationship between the density of pigmentation and the incidence of melanoma on the exposed body sites. Melanin pigment is thought to protect by absorbing the UV (Quevedo et at., 1975) so that the degree of protection would depend on the density of pigment.…”
mentioning
confidence: 96%